Organic Field‐Effect Transistors Based on Ternary Blends Including a Fluorinated Polymer for Achieving Enhanced Device Stability - Tamayo, Adrián; Salzillo, Tommaso; Mas‐Torrent, Marta (Advanced materials interfaces, 2022)
The stability of organic semiconductors (OSCs) is strongly hampered by the presence of water molecules. One approach that has been proved to lead to organic field‐effect transistors with an enhanced performance is the use of blends of OSCs with insulating binding polymers. In this work, the fabrication of OSC thin films based on polymeric ternary blends including a hydrophobic fluorinated polymer is reported as a novel route to engineer long‐term reliable organic field‐effect transistors (OFET) devices. In particular, OFETs based on blends of bis(triisopropylsilylethynyl)pentacene (TIPS) with polystyrene (PS) and poly(pentafluorostyrene) (PFS) are explored. The PS:PFS ratio is tuned in order to find the optimum formulation. It is shown that films including 20% of PFS in the polymeric blend exhibit an improved device performance, which is reflected by a low bias stress and an exceptional environmental stability, without significantly hampering the OFET mobility. This work advocates that adding a small percentage of fluorinated polymers in OSC blends is a promising route to realize more reliable and stable devices without importantly compromising the device mobility. Organic semiconductor thin films based on polymeric ternary blends including a hydrophobic fluorinated polymer are prepared as a novel route to engineer long‐term reliable organic field‐effect transistors. The devices in which 20% of fluorinated polymer is added exhibit an improved bias stress and an exceptional environmental stability, without significantly hampering the charge carrier mobility.